IMPROVING STUDENTS’ SPEAKING ABILITY USING THREE-STEP INTERVIEW FOR BUSINESS ADMINISTRATION TO THE STUDENTS AT BALITAR ISLAMIC UNIVERSITY - Sholikhi, Fu’ad (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2019)
This present research aims to enhance students’ speaking skills three-step interview For Business Administration to The Students at Balitar Islamic University. The study used Classroom Action that is promoted by Latief (2012) and this methodology is used by the researcher in order to answer the student problems which are found in his preliminary study. The subject is the second semester of business administration study program or ESP class. After doing two cycles in his study, the findings show that implementing strategy could give a good contribution to the student speaking skills. It means that this strategy can help them performing a good speaking session by reducing tension in speaking in public, reduce afraid, and shy feeling based on speaking rubric which is used by the researcher in this study.